Microalgae from Antarctic soil - Mohamad Pauzi, Nor Syafawati; Zainal Abidin, Zaima Azira; Zainuddin, Zarina; Chowdhury, Ahmed Jalal Khan (IIUM Press, 2022)
Antarctic microalgae are rich in valuable fatty acids such as omega-3 PUFAs which are significant in the fields of medicine, pharmaceuticals, and aquaculture. Five soil samples from the Antarctic, S6, S10, S11, S21, and S26 were collected and cultured in four different liquid media namely Bold Basal media (BBM), BBM with 3-fold of nitrate and additional vitamins (3N-BBM+V), Jaworski (JM), and Chu 13. After two months, only the S26 soil sample with fine-grained sandy loam texture has positively influenced the revival of microalgae in every nutrient medium except for Jaworski medium (JM). The morphological traits such as spherical shape, smooth cell wall, and parietal chloroplast of the microalgae were observed under light microscopy. The microalgae showed similarities with microalgae belonging to the Chlorophyta group. These findings create further possibilities for further analyses such as molecular identification and chemical compound manipulation.